Changing Fast Food Trends Of People ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2019)
Background: The concept of ready-cooked food for sale is closely connected with urban  development. Fast food is the term given to food that can be prepared and served very quickly.  Fast food industry is one of the world’s fastest growing sectors in food industry. Fast food is the  food item that can be prepared and served very quickly. Food served in fast food restaurants  is offered from a limited menu; it is cooked in bulk in advance and kept hot ,as there is an  order for the dish it is finished and packaged accordingly or available for ready to take away,  or even can be served in the restaurant. Objective: To determine the reasons for emergence  of fast food, To find out the changes in eating trends of people in the age group of 20-30  years, To evaluate the health effects of fast food. Methodology: A Questionnaire was made  and filled up by people in the age group of 20-30 years randomly to check the likes, dislikes  and some more questions were asked related to the fast food and health hazards. Results:More fascinated to western culture and increase in the offers made by the fast food outlets the  frequency of the young people visiting the fast food outlets has increase over the years. The  frequency of their visits also depends on the dispensable income available with them. Some of  them are aware of the long term health hazards of the fast food. Conclusion: From the whole  study, we can conclude that fast food has really evolved and it’s here to stay. Factors such as  globalization and busy life schedules have largely contributed towards their growth.
Keywords: Fast food; Restaurant; Dispensable income; Globalization; Western Culture